Pengaruh Penerapan Sistem Administrasi Perpajakan Modern Terhadap Kepatuhan Wajib Pajak Pribadi di Kantor Pelayanan Pajak (KPP) Pratama Surakarta - Fikriyah, Fikriyah; , Dra. Nursiam, M.H., Ak., CA (2015)
This research aims to understand the influence of the application of tax administration systems compliance modern against individual tax payers in kpp pratama surakarta . This research using methods the questionnaire , the total sample in this research was 50 private taxpayer who enrolled in kpp pratama surakarta .Sample collection method menggunkaan convinience techniques of sampling .A method of the quality of data in a test of the validity of using product moment pearson while reabilitas test using cronbach alpha .Data analysis technique used to test hypotheses include linear analysis worship of idols .All of the data obtained already meet test assumptions test classical namely normality , test and test multikoloniaritas heterokedasitas . Of the research concluded that the organizational structure of variable influential significantly to compliance individual tax payers kpps pratama surakarta.Evidenced by the value of thitung ( 3,791 ) & gt; ttabel ( 2.00 ) and value of significant 0,000 & it; α 0.05.Variable procedure influential organization significantly to compliance individual tax payers in kpp pratama surakarta.Evidenced by the value of thitung ( 2,257 ) & gt; ttabel ( 2.00 ) and value of significant 0,029 & it α 0.05.Variable strategy orgnisasi influential significantly to compliance individual tax payers.Evidenced by the value of thitung ( 2,595 ) & gt; ttabel ( 2.00 ) and value of significant 0,000 & it; α 0.05.Variable culture influential organization significantly to compliance individual tax payers.Evidenced by the value of thitng ( 3,327 ) & gt; ttabel ( 2.00 ) and value of significant 0,000 & it; α 0.05.